Focus : inteligencia emocional - Goleman, Daniel (BookaVivo, 2021)
The importance of achieving focus goes far beyond your own productivity. Deep focus enables you to lead others successfully, find clarity in the midst of uncertainty, and increase your sense of professional satisfaction. However, the forces that challenge sustained focus range from the blurring of phones to office politics to the everyday concerns of life. This book explains how to strengthen your ability to focus, manage your team's attention, and break the cycle of distraction. This volume includes the work of: Daniel Goleman, Heidi Grant, Amy Jen Su, and Rasmus Hougaard. HOW TO BE HUMAN AT WORK. The HBR Emotional Intelligence Series presents intelligent and essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions affect our work lives, practical advice for handling difficult people and situations, and inspiring essays on what it means to attend to our emotional well-being at work. Uplifting and practical, these books outline the soft skills that are critical for ambitious professionals to master.